Między intencjonalnością a zamiarem. Filozoficzne reminiscencje w prawie karnym - Brzezińska, Joanna (PRAWO i WIĘŹ, 2025)
The main premise of this paper was to determine whether the elements of intent, as established in criminal law and accompanying the perpetrator of a crime, can be traced back to the philosophical phenomenon of intentionality. For this purpose, the essence of intentionality was first defined, taking into account the properties that this phenomenon integrates on a philosophical level. Next, the essence of intentionality was characterized by identifying the dimensions that manifest in its construction (the intellectual and volitional dimensions) from the perspective of criminal law. The final part of the study compared the elements and characteristics of the structures studied. On the basis of this comparison, it was shown that the structure of intentionality, as described by philosophers, is reflected in the structure of intention in criminal law. The paper also identifies the characteristics that differentiate the structures studied.